Salinity Stress Tolerance in Plants - Libia Iris Trejo-Téllez (Plants, 2023)
Soil salinization negatively impacts plant development and induces land degradation, thus affecting biodiversity, water quality, crop production, farmers’ well-being, and the economic situation in the affected region. Plant germination, growth, and productivity are vital processes impaired by salinity stress; thus, it is considered a serious threat to agriculture. The extent to which a plant is affected by salinity depends mainly on the species, but other factors, including soil attributes, water, and climatic conditions, also affect a plant’s ability to tolerate salinity stress. Unfortunately, this phenomenon is expected to be exacerbated further by climate change. Consequently, studies on salt stress tolerance in plants represent an important theme for the present Special Issue of Plants. The present Special Issue contains 14 original contributions that have documented novel discoveries regarding induced or natural variations in plant genotypes to cope with salt stress, including molecular biology, biochemistry, physiology, genetics, cell biology, modern omics, and bioinformatic approaches. This Special Issue also includes the impact of biostimulants on the biochemical, physiological, and molecular mechanisms of plants to deal with salt stress and on the effects of salinity on plant nutrient status. We expect that readers and academia will benefit from all the articles included in this Special Issue.